Model updating for fun kart chassis - Mohd Sahril, Mohd Fouzi (2008)
Most of the parts in the vehicle has tendency to vibrate. Chassis is the major part of the lightweight vehicle called fun-kart that has tendency to vibrate and produce uncomfortable driving. This thesis is looks into the application of dynamic correlation techniques for verification of FEA models for fun-kart chassis. The dynamic characteristic of fun-kart chassis such as the natural frequency and mode shape is determined using FEA software called FEMPRO ALGOR. The result from FEA model is validated by EMA result that has performed by previous researcher. Initial result show that the chassis experienced 1stbending mode @ 61.8033 Hz for 1st natural frequency, 1st twist mode @ 72.7612 Hz for 2nd natural frequency, 2nd bending mode @ 111.492 Hz for 3rd natural frequency, and 2nd twist mode @ 125.492 Hz for 4th natural frequency. However there is small discrepancy in terms of frequency. Thus, the model updating of fun-kart chassis model has been carried by adjusting the selective properties such as Modulus Young and mass density in order to get better agreement in natural between FEA and EMA. Finally, the modification of updated FE fun-kart chassis model has been suggested such as by considers adding the thickness. The percentage different error achieved is < 10% for natural frequency between FEA and EMA.